2012
DOI: 10.1371/journal.pcbi.1002403
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Evolution of Novel Enzyme Functions within Structurally Defined Protein Superfamilies

Abstract: In order to understand the evolution of enzyme reactions and to gain an overview of biological catalysis we have combined sequence and structural data to generate phylogenetic trees in an analysis of 276 structurally defined enzyme superfamilies, and used these to study how enzyme functions have evolved. We describe in detail the analysis of two superfamilies to illustrate different paradigms of enzyme evolution. Gathering together data from all the superfamilies supports and develops the observation that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 43 publications
(49 reference statements)
1
74
0
Order By: Relevance
“…By contrast, the low sequence similarities across this superfamily make it practical to generate sequencebased phylogenies only across subsets of the superfamily. Consequently, superfamilies such as this are missed by efforts to marry structural information with sequence-based phylogenies for superfamilies in or beyond the twilight zone of sequence similarity (20 -30% pairwise sequence identity) (20,21). We summarize briefly how these databases and phylogenies inform current classification of the ferritin-like superfamily.…”
Section: Current Classification Of Ferritin-like Proteins Across Majormentioning
confidence: 99%
“…By contrast, the low sequence similarities across this superfamily make it practical to generate sequencebased phylogenies only across subsets of the superfamily. Consequently, superfamilies such as this are missed by efforts to marry structural information with sequence-based phylogenies for superfamilies in or beyond the twilight zone of sequence similarity (20 -30% pairwise sequence identity) (20,21). We summarize briefly how these databases and phylogenies inform current classification of the ferritin-like superfamily.…”
Section: Current Classification Of Ferritin-like Proteins Across Majormentioning
confidence: 99%
“…The evolution of enzymes involves sequence changes that are frequently localized at loop regions and thus reveal their role in protein evolution and in the diversification of numerous enzyme families and superfamilies. 3 Over the past few years, a surge of interest from the scientific community has brought the study of loopstheir flexibility and impact on enzyme functionto the forefront of biocatalysis. Most of the activity in this field so far has centered on the role of surface and lid loops that cover the active site and their functional role in substrate and cofactor binding, protein− protein interaction, and stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been suggested that an ancestral pool of peptide modules may have given rise to the first protein folds that were dispersed into different superfamilies (2)(3)(4). Some of these peptide modules are part of the limited set of building blocks (i.e., the "redox enzyme construction kit") that gave rise to many oxidoreductases (5).…”
mentioning
confidence: 99%